The SDGs and the bio-economy: fostering land-grabbing in Africa. Issue 164 (2nd April 2020) - Ashukem, Jean-Claude N.
ABSTRACT: This article analyses the contributory role of the bio-economy and the UN General Assembly Sustainable Development Goals in facilitating and fostering land-grabbing in sub-Saharan Africa. It argues that with the rapidly increasing demand for land and the use of agricultural produce for food and energy purposes, the bio-economy, together with the Sustainable Development Goals, has inexorably exacerbated the practice of land-grabbing in sub-Saharan Africa, where land is considered to be abundant, empty and unused. Sub-Saharan Africa has again been perceived primarily as a steady supplier of land for the production of food and non-food crops.